Radius of strongly starlikeness for certain analytic functions - Oh Sang Kwon; Shigeyoshi Owa (International Journal of Mathematics and Mathematical Sciences)
For analytic functions f(z)=zp+ap+1zp+1+⋯ in the open unit disk U and a polynomial Q(z) of degree n>0, the function F(z)=f(z)[Q(z)]β/n is introduced. The object of the present paper is to determine the radius of p-valently strongly starlikeness of order γ for F(z).